Development of problem-posing and solving worksheets to facilitate students' mathematical creative thinking - Rahmaini, Annisa; Suanto, Elfis; Syofni (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
One of the goals of mathematics education in the Kurikulum Merdeka is to develop students' creative thinking skills in mathematics. However, current evidence shows that students' creative thinking skills remain low. This issue arises because students are not regularly exposed to contextual problems that require creativity, argumentation, and reasoning. Moreover, the use of Student Worksheets is still limited and does not adequately foster students' mathematical creative thinking skills. In response, this research aims to develop a Student Worksheet based on the Problem Posing and Solving Learning Model, commonly known as the Jucama model, focused on the Pythagorean theorem content to enhance the mathematical creative thinking skills of phase D students. The research follows a development approach using the 4D model, which includes the stages of define, design, develop, and disseminate. Data were collected using questionnaires, involving 15 ninth-grade students from SMP 22 Pekanbaru in a small group trial. The validity of the worksheet, as evaluated by experts, averaged 92.5%, categorizing it as very valid. The practicality of the worksheet was rated at 83.33%, also categorized as very practical. These results indicate that the worksheet developed using the Jucama model on the Pythagorean theorem content is both valid and practical for facilitating the creative thinking skills of phase D students.